Adsorption of Sulfate Ions (SO42-) from Distillery Spent Wash Using Biochar Derived from Digestate Biogas - Novia Nadzifah; Shabrina Nur Mutia M; Ketut Sumada (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Sulfate (SO?²?) is a major inorganic pollutant in distillation washwater with concentrations of 4,000–6,000 mg/L and the potential to form H?S during anaerobic processes. This study investigated sulfate removal using biochar derived from biogas digestate. The biochar was produced by carbonization at 600 °C for 1.5 h and applied as an adsorbent with masses of 1–3 g and contact times of 20–100 min. BET, SEM-EDX, and FTIR analyses showed that the biochar had a mesoporous structure with a surface area of 140 m²/g, pore volume of 0.155 cm³/g, pore diameter of 4.43 nm, mineral content of Ca, K, and Mg, and active functional groups. Adsorption efficiency increased until reaching an optimum at 2 g adsorbent and 60 min contact time with an efficiency of 88.7605%, then decreased due to adsorption equilibrium and ion competition. Isotherm analysis indicated that the adsorption process followed the Langmuir model with a maximum adsorption capacity of 232.558 mg SO?²?/g, indicating monolayer adsorption on a homogeneous surface. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 7: Affordable and Clean EnergySDG 12: Responsible Consumption and Production